Preface - Merkevičius, Algimantas (Archaeologia Lituana, 2016)
In the hands of a kind reader is, at the first glance, ordinary, but actually significantly changed, the 16th volume of “Archaeologia Lituana”. One of the most important changes in this volume is the appointment of a new chief editor. During the joint meeting of the editorial board of “Archaeologia Lituana” and the Department of Archaeology that took place on 6th February 2015, the long-time chief editor prof. Habil. dr. Mykolas Michelbertas stepped down voluntarily and assoc. prof. dr. Algimantas Merkevičius was elected. On this occasion, I would like to use this opportunity to thank the professor for many years of hard and unremitting work, publishing one volume every year, under not always favourable circumstances. Samogitian stubbornness, perseverance and great authority undoubtedly helped with this complex and responsible task. [...]